Pengaruh Model Pembelajaran Kooperatif Tipe Script dengan Demonstrasi terhadap Hasil Belajar Fisika - Hajar H.U. Sanggayu; Darsikin Darsikin; Amiruddin Hatibe (Jurnal Kreatif Online, 2021)
This study aims to determine whether there was an effect of the Script type cooperative learning model with demonstration on students' physics learning outcomes. This research was a quasi-experimental research using the non-equivalent control group design. The instrument used was a test of physics learning outcomes in the form of multiple choice with a total of 23 questions. Based on the results, the average pretest score of the experimental class students' physics learning outcomes was 8.14, while the average posttest score was 15.79. For the control class, the average pretest score was 7.73, while the posttest average was 12.19. Analysis of the test data was carried out using a two-party t-test statistical technique to test the difference in the mean scores of students' physics learning outcomes with a significant level of = 0.05. The results obtained are tcount = 8.00 and ttable = 2.02. It means that there was an influence of Script-type cooperative learning model with demonstration on students' physics learning outcomes.